MEMAJUKAN KEPEMIMPINAN PEREMPUAN DALAM LEMBAGA PENDIDIKAN: TANTANGAN, STRATEGI, DAN DAMPAK TRANSFORMATIF (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Women’s leadership in education has become an important issue in advancing gender equality. This study aims to examine the challenges, strengthening strategies, and impacts of women’s leadership through a literature review approach. The findings indicate that women still face various barriers, including gender bias, dual roles between domestic and professional responsibilities, limited access to networks and career support, as well as the influence of patriarchal culture and the glass cliff phenomenon. To address these challenges, strengthening strategies are needed, such as capacity building through training, strengthening professional networks, and implementing participatory and transformational leadership styles. Furthermore, women’s leadership has a positive impact in creating inclusive educational environments, fostering collaborative working relationships, developing student-centered policies, and promoting ethical and empathetic decision-making. Therefore, women’s leadership plays a strategic role in driving more humane, equitable, and sustainable educational transformation.